Effects of RGO on the Microstructure and Properties of Ni - P Electroless Coating - LU Min (Cailiao Baohu)
At present, there are few researches on the composite materials related to reduced graphene oxide (RGO) for composite plating protection of low carbon steel. Ni - P - reduced graphene oxide composite coating was prepared on Q235 steel by electroless composite plating. The crystal structure, morphology and hardness of the Ni - P - RGO composite coating at different added content of RGO were analyzed using X - ray diffractometer, scanning electron microscope and microhardness tester. The corrosion rate of Ni - P - RGO composite coating was measured by total immersion corrosion test. The electrochemical corrosion behavior of Ni - P - RGO composite coating in 3.5% NaCl solution was examined by polarization curves and electrochemical impedance spectroscopy. Result showed that the Ni - P - RGO composite coating was amorphous. The hardness test, immersion corrosion test, polarization curves and electrochemical impedance spectroscopy result indicated that when the added content of RGO was 60 mg/L, Ni - P - RGO composite coating had the best hardness and corrosion resistance.